2021
DOI: 10.1002/celc.202100329
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction of 4‐Nitrobenzyl Phenyl Thioether for Activation and Capture of CO2

Abstract: In this work, a new simple molecule, 4-nitrobenzyl phenyl thioether (1), is prepared and used for controlling and tuning CO 2 reactivity in function of the electrode potential. The first part of the study is devoted to determining the electrochemical reduction mechanism of 1 in N,N-dimethylformamide under nitrogen. The compound shows a first reversible one-electron transfer process, whereas the reaction cleavage of the CÀ S bond takes place after a second electron transfer process through a stepwise mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Likewise, it cannot be ruled out that CO 2 radical anions can act as reductive electron transfer mediators for certain substrates as reported for electroreduction of benzoate esters and thioethers. [16,90] It can be noted that alkyl carbonates were not observed in the reaction mixture by NMR, suggesting a distinctly different mechanism for the deoxygenative carboxylation compared to the in situ formed carbonate intermediate reported by Senboku and co-workers. [73] It is well established in fuel cell applications that borohydride compounds can undergo electrooxidation to generate H 2 , [81][82][83]91,92] and bubble formation at the anode suggested that this is a likely path in the present system.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Likewise, it cannot be ruled out that CO 2 radical anions can act as reductive electron transfer mediators for certain substrates as reported for electroreduction of benzoate esters and thioethers. [16,90] It can be noted that alkyl carbonates were not observed in the reaction mixture by NMR, suggesting a distinctly different mechanism for the deoxygenative carboxylation compared to the in situ formed carbonate intermediate reported by Senboku and co-workers. [73] It is well established in fuel cell applications that borohydride compounds can undergo electrooxidation to generate H 2 , [81][82][83]91,92] and bubble formation at the anode suggested that this is a likely path in the present system.…”
Section: Resultsmentioning
confidence: 79%
“…As such, it cannot be ruled out that the C−C bond formation may also proceed via radical‐radical coupling of benzylic open shell intermediates and CO 2 radical anions (ESI, Section 12) and that the contribution of different pathways is substrate dependent. Likewise, it cannot be ruled out that CO 2 radical anions can act as reductive electron transfer mediators for certain substrates as reported for electroreduction of benzoate esters and thioethers [16,90] . It can be noted that alkyl carbonates were not observed in the reaction mixture by NMR, suggesting a distinctly different mechanism for the deoxygenative carboxylation compared to the in situ formed carbonate intermediate reported by Senboku and co‐workers [73] …”
Section: Resultsmentioning
confidence: 87%
“…This effort is in an early stage. In fact, many of the stimulus-responsive adsorbent materials also require high energy to release captured CO 2 and regenerate the original state. ,, Electric-swing adsorption (ESA) can minimize such energy losses in stimuli-responsive adsorbent materials because the adsorbent materials can be operated with much higher efficiency than the TSA and pressure-swing adsorption (PSA) processes. …”
Section: Introductionmentioning
confidence: 99%
“…Actually, the chemical synthesis of carboxylic acids and their derivatives (e. g., esters or amides) imply the use of many reagents, catalysts [33] or organolithium compounds [34] at mild or strong conditions [35,36] . In this context, the electrochemical carboxylation of organic molecules to produce carboxylic acids by fixing carbon dioxide has emerged during the last years as an efficient green route compared to conventional chemical synthetic methods, especially since this process can be performed efficiently under mild conditions at atmospheric pressure and avoiding the use of additional reagents [37–42] . One of the most popular electrocarboxylation strategies of organic compounds is based on the in situ formation of a carbanion via reduction, which in turn undergoes a nucleophilic addition to CO 2 to yield the carboxylate functional group (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…[35,36] In this context, the electrochemical carboxylation of organic molecules to produce carboxylic acids by fixing carbon dioxide has emerged during the last years as an efficient green route compared to conventional chemical synthetic methods, especially since this process can be performed efficiently under mild conditions at atmospheric pressure and avoiding the use of additional reagents. [37][38][39][40][41][42] One of the most popular electrocarboxylation strategies of organic compounds is based on the in situ formation of a carbanion via reduction, which in turn undergoes a nucleophilic addition to CO 2 to yield the carboxylate functional group (Figure 2). [43] The success of this approach is strongly related to the stability (i. e., lifetime) of the anion formed in the electrolytic medium.…”
Section: Introductionmentioning
confidence: 99%